Integrasi Kewenangan Penyidik Dalam Sengketa Fraud Pada Sektor Lembaga Keuangan Syariah - Alladuniah, Muhammad Ali; Afif Syafiuddin (Fawaid : Sharia Economic Law Review, 2025)
This study examines the synchronization of investigative authority between the Indonesian National Police (Polri) and the Civil Servant Investigators (PPNS) of the Financial Services Authority (OJK) in handling fraud cases within Islamic Financial Institutions (LKS). Using a normative legal method with statutory, conceptual, and case approaches, the research analyzes the regulatory framework governing investigative authority as stipulated in the Criminal Procedure Code (KUHAP), the Financial Sector Development and Strengthening Law (P2SK Law), Government Regulation No. 5 of 2023, and OJK Regulations No. 16 of 2023 and No. 12 of 2024. The findings reveal that PPNS OJK holds sectoral authority to investigate regulatory violations and fraud offenses in the financial services sector, while Polri retains the primary role in investigating general criminal offenses and executing coercive measures in accordance with KUHAP. However, overlapping and ambiguous jurisdictions pose legal and operational challenges. Therefore, an effective synchronization model is needed through the establishment of joint investigation teams, coordinated standard operating procedures, mechanisms for resolving jurisdictional disputes, secure data-sharing systems, and cross-agency training between Polri and PPNS OJK. This model is expected to strengthen law enforcement, enhance institutional accountability, and safeguard the integrity of the national Islamic financial system in addressing fraud-related crimes.   Keywords: Authority, Investigation, Fraud, Islamic Financial Institutions.